2020
DOI: 10.1200/jco.2020.38.4_suppl.103
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study investigating cabozantinib in patients with refractory metastatic colorectal cancer (AGICC 17CRC01).

Abstract: 103 Background: Therapeutic resistance to antiangiogenics in metastatic colorectal cancer (mCRC) inevitably develops via multiple mechanisms including upregulation of the MET kinase pathway. Cabozantinib, an oral multityrosine kinase inhibitor targeting MET, AXL, and VEGFR, demonstrated significant anti-tumor activity in CRC xenograft and cell line models. Methods: A single-arm, two-stage phase II study was conducted at 7 AGICC centers nationwide. 44 patients (pts) with mCRC who had progressed on or were into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In all, 18 phase II studies and one phase I study evaluated patients with various types of tumor. [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] In all but one of these studies, 79 the cabozantinib dose was 60 mg. In one study in 50 patients with relapsed or refractory metastatic urothelial carcinoma (mUC), the primary endpoint, ORR (95% CI), was 19% (9-34%).…”
Section: Evidence From Nonrandomized Phase I and Ii Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 18 phase II studies and one phase I study evaluated patients with various types of tumor. [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] In all but one of these studies, 79 the cabozantinib dose was 60 mg. In one study in 50 patients with relapsed or refractory metastatic urothelial carcinoma (mUC), the primary endpoint, ORR (95% CI), was 19% (9-34%).…”
Section: Evidence From Nonrandomized Phase I and Ii Clinical Studiesmentioning
confidence: 99%
“…One study, in 44 patients with metastatic colorectal cancer, had 12-week PFS rate as the primary endpoint, which was 34%. 92 A retrospective analysis of phase II data measured OS in 108 patients with recurrent glioblastoma, in whom antiangiogenic therapy had not previously failed. After treatment with cabozantinib 100 mg or 140 mg QD, median OS was 11.0 months.…”
Section: Evidence From Nonrandomized Phase I and Ii Clinical Studiesmentioning
confidence: 99%
“…Despite encouraging activity of cediranib in a phase I clinical study, it was not further investigated for patients with CRC [25]. Cabozantinib treatment was found to be safe and demonstrated encouraging efficacy as 34% of the heavily pre-treated patients with CRC achieved ≥12 weeks PFS in an ongoing phase II clinical study [26]. Another multi-kinase inhibitor, lenvatinib did not demonstrate cytotoxic but rather cytostatic effect in vitro and gave variable results in vivo [27,28].…”
Section: Tkis As Monotherapymentioning
confidence: 99%
“…Apatinib is a highly selective oral inhibitor of VEGFR2 [ 109 ], with a putative activity as a multidrug resistance reverser as well [ 110 ]. A single-arm phase II trial of this compound in Chinese chemorefractory mCRC patients reported a DCR of 69% and a median OS of 9.1 months, with hypertension (13%), hand-foot syndrome (10%), and thrombocytopenia (10%) being the most frequent grade ≥3 AEs.…”
Section: Recent Developments and Ongoing Clinical Trialsmentioning
confidence: 99%